Methodological approaches to the formation and development of the economic potential of transnational corporations in conditions of turbulence and risk - Puzyrova, P.P.; Pylypenko, O.O.; Honcharuk, Ye.L.; Пилипенко, Ольга Олегівна (Державний Науково-дослідний інститут інформатизації та моделювання економіки, 2024)
It has been established that transnational corporations (TNCs) are central to the modern global economy and their impact on the economic development of countries is extremely large and powerful. However, the conditions of turbulence and risk pose obstacles to TNCs that require new methodological approaches to the formation and development of their economic potential. Methodological approaches to the development of TNCs’ economic potential should take into account rapid changes in the external environment, which requires new management strategies, adaptation to conditions of instability and risk. The economic potential of transnational corporations is a set of material, financial, human, innovative, informational, managerial, production, technological and other resources that a company uses to ensure its sustainable development and increase its competitiveness in the global market. The main components of the economic potential of a TNC are: financial potential; innovation potential; human resources potential; and resource potential. The formation and development of TNCs’ economic potential in the context of turbulence and risk are conditioned by the following factors: globalization and market integration; technological innovations; competition; political and economic risks; financial stability; demographic changes; socio–cultural factors; environmental requirements; adaptability and flexibility; cooperation and partnership. Besides, the formation and development of the economic potential of TNCs in the context of turbulence and risk requires compliance with a number of principles that allow TNCs not only to survive but also to develop in the face of uncertainty and risks that are characteristic of the modern global business environment. It is determined that the main methodological approaches are: risk diversification; flexibility of strategies; investment in innovation; effective management of human resources; adaptive planning; development of partnerships; implementation of sustainability principles
Keywords: transnational corporations; economic potential; turbulence and risks; efficiency; formation and development; methodological approaches; strategies; globalization; adaptation